2016
DOI: 10.1111/ajt.13709
|View full text |Cite|
|
Sign up to set email alerts
|

A Risk Index for Living Donor Kidney Transplantation

Abstract: Choosing between multiple living kidney donors, or evaluating offers in kidney paired donation, can be challenging because no metric currently exists for living donor quality. Furthermore, some deceased donor kidneys can result in better outcomes than some living donor kidneys, yet there is no way to compare them on the same scale. To better inform clinical decision-making, we created a living kidney donor profile index (LKDPI) on the same scale as the deceased donor KDPI, using Cox regression and adjusting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 30 publications
5
137
0
Order By: Relevance
“…The recipient and donor age were fitted using splines as described above. The C-statistic for the 5-year model is 0.64, which compares favorably with other models for graft survival (2,28,29). It should be noted that the C-statistic estimates the probability that the model would allow us to correctly predict which of two randomly chosen individuals would fail first.…”
Section: Using Estimates To Assess and Compare Donor-recipient Outcomesmentioning
confidence: 79%
“…The recipient and donor age were fitted using splines as described above. The C-statistic for the 5-year model is 0.64, which compares favorably with other models for graft survival (2,28,29). It should be noted that the C-statistic estimates the probability that the model would allow us to correctly predict which of two randomly chosen individuals would fail first.…”
Section: Using Estimates To Assess and Compare Donor-recipient Outcomesmentioning
confidence: 79%
“…Though evidence exists for deceased donor graft longevity, less has been published for living donors. 2,10,11 Brennan et al 12 looked at over 8500 LDKTs calculating a suboptimal graft function score equating worse outcome with recipient serum creatinine 1.5 mg/dL or greater at 1 year. Aside from this being a crude measure of graft longevity, it does not provide concrete information how many added years of function 1 donor provides over another.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a LDKT risk index was published where it was concluded that donor age, body mass index, race, cigarette use, and HLA B and DR mismatches were associated with risk of graft loss. 2 We identified some similar factors using KLYs.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of risks to both the recipient and the donor. Elevated donor BMI is associated with an increased risk of allcause graft loss [34]. Additionally, recipients of transplants from obese donors are more likely to experience DGF [35].…”
Section: Transplantation With An Obese Live Donor Kidneymentioning
confidence: 99%